2020
DOI: 10.15763/issn.2470-9670.2020.v4.i2.a67
|View full text |Cite
|
Sign up to set email alerts
|

Simple or complex? Consumer response to display signs

Abstract: Retail signage provides information from the marketer to facilitate product purchase. An increase in sign information creates greater sign complexity, which raises the question: for consumer product choices, what quantity of information is helpful versus overwhelming? We hypothesize that consumers would allocate more visual attention to complex signs and that sign complexity would be a predictor of likeliness to buy (LTB). Five experts rated 105 real garden center signs for complexity and five low, moderate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Furthermore, retail sign complexity influences visual attention. For example, study participants viewing garden center signs fixated more (by fixation counts) on signs with moderate visual complexity compared to low or high complexity signs, and had higher buy ratings [35]. This was perhaps explained by greater processing fluency of the moderate complexity signs (compared to highly complex signs), but containing more information compared to the low complexity signs, which contributed little to the purchase decision.…”
Section: Visual Information Processingmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, retail sign complexity influences visual attention. For example, study participants viewing garden center signs fixated more (by fixation counts) on signs with moderate visual complexity compared to low or high complexity signs, and had higher buy ratings [35]. This was perhaps explained by greater processing fluency of the moderate complexity signs (compared to highly complex signs), but containing more information compared to the low complexity signs, which contributed little to the purchase decision.…”
Section: Visual Information Processingmentioning
confidence: 94%
“…What goes unseen goes unsold, thus, the use of eye-tracking devices has become more commonplace in consumer research [30,[35][36][37]. Within a scene or display, areas of interest (AOIs) are identified, and visual metrics can be extracted by AOI.…”
Section: Analysesmentioning
confidence: 99%
“…The rejection of H4 and H5 may provide indirect support for the hypotheses that external factors may influence decision consistency in plant purchases. Aspects of the product such as color, signage, viability of the plant, and other retail environmental cues may be “pushing” the product information into the consumer’s decision-making process and, as a result, be the solidifying factor of purchase intent consistency rather than aspects about the consumer themselves [ 1 , 2 , 3 , 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, each purchase intention can be influenced by consumers’ degrees of certainty, and if this certainty outweighs the purchase intention, it can lead to a lost purchase. Previous research regarding plant purchases showed that factors influencing purchase intention include having a guarantee of the viability of the plant, price discounts, and clear, strategic signage [ 1 , 2 , 3 ]. However, these are all examples of external influences on a purchase decision.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating the communication effectiveness of signage, there are numerous consumer responses that merit consideration, including attention (Kellaris & Machleit, 2016;Knuth et al, 2020;Wu et al, 2020), affective reaction (Kellaris et al, 2020), and trust (Isaac, 2020). In our research, we focus specifically on consumers' self-reported evaluation of signage, which we operationalize as their liking of the billboard.…”
Section: Introductionmentioning
confidence: 99%